Ordinance No. 408, §§ 10, 11, 28, & 29, Anacortes City Council (1909) (Anacortes, Washington). - (:unkn) unknown (General Publisher, 1909)
Every person, except a peace officer, who shall within the city of Anacortes, have concealed upon his person or who shall furtively carry, or conceal any dagger, dirk, knife, pistol, or other dangerous weapon shall be guilty of a misdemeanor.Every person who shall within the city of Anacortes, manufacture, sell or dispose of or have in his possession any instrument or weapon of the kind known as slung shot, sand club or metal knuckles, excepting a peace officer, shall be guilty of a misdemeanor...Any person who shall within the city of Anacortes sell or give or permit to be sold or given to any person under the age of eighteen years any revolver, pistol, or toy pistol, xxxx xxxxx1 shall be guilty of a misdemeanor.Any person who shall within the city of Anacortes discharge any firearms, gun, cannon, pistol, air gun, bomb, or otherx1 dangerous explosive without having first obtained the written permission of the mayor thereof, shall be guilty of a misdemeanor."
--
Keywords: CARRY - CONCEALED